Predictors of Clinical Success After Transcatheter Paravalvular Leak Closure: An International Prospective Multicenter Registry. (18th October 2022) - Hascoët, Sébastien; Smolka, Grzegorz; Blanchard, David; Kloëckner, Martin; Brochet, Eric; Bouisset, Frederic; Leurent, Guillaume; Thambo, Jean-Benoit; Combes, Nicolas; Dumonteil, Nicolas; Bauer, Fabrice; Nejjari, Mohammed; et al.
Abstract : Background: Transcatheter closure of a symptomatic prosthetic paravalvular leak (PVL) is feasible, but there is presently no conclusive evidence to show consistent efficacy. We aimed to identify predictors of clinical success after transcatheter PVL closure. Methods: Consecutive patients referred to 24 European centers for transcatheter PVL closure in 2017 to 2019 were included in a prospective registry ( Fermeture de Fuite ParaProthétique, FFPP). Clinical success was absence of any of the following within 1 month: re-admission for heart failure, blood transfusion, open-heart valvular surgery, and death. Results: We included 216 symptomatic patients, who underwent 238 percutaneous PVL closure procedures on the mitral (64.3%), aortic (34.0%), or tricuspid (1.7%) valve. Symptoms were heart failure, hemolytic anemia, or both in 48.9%, 7.8%, and 43.3% of patients, respectively. One, 2, and 3 leaks were treated during the same procedure in 69.6%, 26.6%, and 3.8% of patients, respectively. The PVL was pinpoint or involved 1/8 or 1/4 of the valve circumference in 18.6%, 52.4%, and 28.1% of cases, respectively. The most frequently used devices were the Vascular Plug 3, Ventricular Septal Defect Occluder, Vascular Plug 2, and Paravalvular Leak Device (45.0%, 16.6%, 14.2%, and 13.6% of cases, respectively). Successful device(s) implantation with leak reduction to ≤grade 2 was obtained in 85.0% of mitral and 91.4% of aortic procedures, respectively ( P =0.164); with major periprocedural adverse event rates of 3.3% and 1.2%, respectively ( P =0.371); and clinical success rates of 70.3% and 88.0%, respectively ( P =0.004). By multivariate analysis, technical failure, mechanical valve, and hemolytic anemia were independently associated with absence of clinical success (odds ratios [95% CIs], 7.7 [2.0–25.0]; P= 0.002; 3.6 [1.1–11.1]; P =0.036; and 3.7 [1.2–11.9]; P =0.025; respectively). Conclusions: Transcatheter PVL closure is efficient and safe in symptomatic patients but is associated with a lower clinical success rate in patients with hemolysis and/or a mechanical valve. Registration: URL: https://www.clinicaltrials.gov ; Unique identifiers: NCT05089136